Self-discrepancy and elaboration of self-conceptions as factors influencing reactions to feedback - Dauenheimer, Dirk; Stahlberg, Dagmar; Petersen, Lars-Eric (European journal of social psychology, 1999)
Previous research examined the predictions of the self‐enhancement theory and the self‐consistency theory regarding reactions to self‐relevant feedback. In the present study two circumstances that are supposed to moderate self‐enhancement and self‐consistency motives have been examined: the elaboration of a self‐conception and the discrepancy between the actual self and a personal standard. One hundred and fourteen participants received either positive, consistent, or negative feedback regarding their results on a personality test. Affective and cognitive reactions to fictitious feedback were measured as dependent variables. In accordance with prior empirical evidence, affective reactions followed the self‐enhancement theory and cognitive reactions were in line with the self‐consistency theory. Moreover, affective and cognitive reactions were influenced by the elaboration of a self‐conception and the discrepancy between the actual self and a personal standard as predicted. Regarding affective reactions, the predictions of the self‐enhancement theory were more clearly supported when self‐conceptions were less elaborated or when people perceived a high self‐discrepancy. Regarding cognitive reactions, the predictions of the self‐consistency theory were more clearly supported when self‐conceptions were highly elaborated or when people perceived a low self‐discrepancy. Copyright © 1999 John Wiley & Sons, Ltd.